Analysis of understanding and application of football actions - Muslim, Bikari Saiful; Pramdhan, Kartono; Valentino, Ricky Ferrari (STKIP Paasundan Press, 2025)
This study aims to analyze the understanding and application of basic football actions, especially passing and first touch techniques, in STKIP Pasundan Cimahi Football UKM athletes. These basic techniques are considered important because they affect the effectiveness of the game and the team's success in building attacks. This study uses a quantitative descriptive method with a one-shot case study approach, where data collection is carried out once through direct observation of 10 athletes. The research instrument is an observation sheet containing indicators of passing and first touch skills. The results of the analysis show that the passing technique value tends to be higher than the first touch, but the results of the Wilcoxon Signed Ranks Test show no statistically significant difference between the two (p> 0.05). Thus, it can be concluded that the athletes have a good understanding and application of football actions, especially in the passing aspect. This study recommends increasing the intensity of structured training for the first touch aspect in order to achieve a balance in basic technical abilities as a whole